1991
DOI: 10.1073/pnas.88.15.6745
|View full text |Cite
|
Sign up to set email alerts
|

Induction of soybean vegetative storage proteins and anthocyanins by low-level atmospheric methyl jasmonate.

Abstract: Soybean seedlings were exposed to atmo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
95
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 31 publications
8
95
1
1
Order By: Relevance
“…In Arabidopsis, OPDA can activate wound-induced gene expression in the absence of JA (Taki et al, 2005). In parsley (Petroselinum crispum), soybean (Glycine max), and bean, either OPDA or JA promotes the synthesis of flavonoids and the expression of their biosynthetic genes (Franceschi and Grimes, 1991;Dittrich et al, 1992;García-Ponce and Rocha-Sosa, 2000). In addition to oxylipins, ethylene has also been implicated in the activation of systemic plant defenses in response to pathogens (Penninckx et al, 1998) and wounding (O'Donnell et al, 1996).…”
mentioning
confidence: 99%
“…In Arabidopsis, OPDA can activate wound-induced gene expression in the absence of JA (Taki et al, 2005). In parsley (Petroselinum crispum), soybean (Glycine max), and bean, either OPDA or JA promotes the synthesis of flavonoids and the expression of their biosynthetic genes (Franceschi and Grimes, 1991;Dittrich et al, 1992;García-Ponce and Rocha-Sosa, 2000). In addition to oxylipins, ethylene has also been implicated in the activation of systemic plant defenses in response to pathogens (Penninckx et al, 1998) and wounding (O'Donnell et al, 1996).…”
mentioning
confidence: 99%
“…Previously it was shown that the plant growth regulator methyl jasmonate causes induction of VSP gene expression and accumulation of VSP proteins Franceschi and Grimes, 1991;Staswick et al, 1991). Figure 6 shows extracts of leaves, cotyledons, and stems of seedlings exposed to different concentrations of atmospheric methyl jasmonate.…”
Section: Methyl Jasmonate Induction Of Svlmentioning
confidence: 99%
“…Levels of SVL are much lower than those of VSP under a11 conditions investigated, arguing against a similar function for SVL. SVL is the first lectin shown to be regulated by methyl jasmonate, which has previously been shown to regulate expression of VSP genes (Franceschi and Grimes, 1991;Mason et al, 1992). Methyl jasrnonate has been implicated in plant responses to physiological stresses such as wounding, herbivory, and water deficit (Staswick, 1992), suggesting that SVL may serve a function relating to these responses.…”
Section: Reaction Of Svl-hsp Conjugatementioning
confidence: 99%
See 2 more Smart Citations